Ultrasound‐guided transcervical forceps extraction of unruptured interstitial pregnancy. Issue 10 (20th May 2013) - Ahn, J‐W; Lee, S‐J; Lee, SH; Kang, SP; Won, H‐S
<x xml:space="preserve">Abstract</x> This report introduces a method for ultrasound‐guided transcervical forceps extraction (UTCE) of unruptured interstitial pregnancies; this method does not necessitate elective caesarean delivery for future pregnancies. This report also compares this technique with conventional methods. A retrospective review was conducted involving 16 women treated for interstitial pregnancies. Among these women, UTCE was successfully performed in six of 16 women, with only one woman requiring additional intervention; conventional treatment was performed in the other ten women. UTCE is a safe, effective and minimally invasive option for treating interstitial pregnancies and should be considered as an alternative treatment modality.